8 - La guerre dans les médias, les médias dans la guerre en Côte d’Ivoire: https://doi.org/10.4314/ad.v34i2.57377 - Blé, Raoul Germain (Africa Development, 2009)
This paper proposes a reflection on a particular type of informative media discourse: opinion journalism, which has been very prominent in Côte d’Ivoire since the war on September 2002 which split the country into two parts. The paper, therefore, uses a constructivist approach based on the obvious fact that journalisitic information is the product of a created entity. The issue of “the media in the war, the war in the media” is a major issue for public debate, for it is established as a new public space in the formation and expression of opinions. In the Ivorian context, information is the dominant paradigm and the informant is the activist-journalist whose relationship to his/her audience is built on a mode mostly based on membership, in the ideological meaning of the term. The journalistic discourse adds to its traditional function, which is to inform, new conditioning and mobilization functions that make it fully an ideological space of full membership.